Comparative Analysis of Imaging Sensitivity of Positron Emission Mammography and Whole-Body PET in Relation to Tumor Size. (January 2015) - Yamamoto, Yayoi; Ozawa, Yukihiko; Kubouchi, Kouichi; Nakamura, Seigo; Nakajima, Yasuo; Inoue, Tomio
Abstract : Objective: Positron emission mammography (PEM) consists of a dedicated PET scanner for breast imaging with a higher spatial resolution than whole-body PET (WBPET) scanners. This study compared the imaging sensitivity of PEM with WBPET in relation to tumor size. Methods: Fifty-four Japanese women younger than 50 years with histologically confirmed breast lesions were retrospectively enrolled. Positron emission mammography and WBPET were conducted on the same day. Positron emission mammography and WBPET images were blindly evaluated and compared with histopathology. Tumors were classified into 3 groups based on size as follows: group 1, 1 cm or smaller; group 2, 1 to 2 cm; and group 3, larger than 2 cm. The sensitivities of PEM and WBPET were compared in overall subjects and in each size group. Results: In visual analysis, the overall imaging sensitivity was 78.6% (33/42) for PEM and 47.6% (20/42) for WBPET. The overall sensitivity of PEM was significantly higher than that of WBPET ( P < 0.001). The differences in sensitivities between PEM and WBPET were larger in smaller tumors: group 1 (66.7% vs 13.3%), group 2 (63.4% vs 36.4%), and group 3 (100.0% vs 87.5%). The sensitivity of PEM was significantly higher than that of WBPET in group 1 ( P = 0.008); however, no significant differences were seen in group 2 ( P = 0.500) or group 3 ( P = 0.250). Overall, the imaging specificity of PEM and WEBPET was 90.6% (60/66) and 93.9% (62/66), respectively. Conclusions: The imaging sensitivity of PEM was higher than that of WBPET in Japanese women younger than 50 years. Positron emission mammography showed significant sensitivity in tumors smaller than 1 cm, which has been a weak point for WBPET.